1995
DOI: 10.1123/ijsn.5.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Female Collegiate Heavyweight Rowers

Abstract: The purpose of this study was to evaluate the adequacy of dietary intake in 16 female heavyweight rowers during the sprint racing phase of the season. Caloric intake for the rowers was 2,633 kcal/day, lower than expected given the training regimen of these athletes. On average, rowers consumed below-optimal levels of carbohydrate. Protein intake was satisfactory but fat intake was higher than recommended. For the majority of rowers, micronutrient intake met the RDA. However, calcium, zinc,, andfell short of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Although the NP consumed more kilocalories than the CP, both groups failed to consume the recommended kilocalories for female volleyball players of 44 kcal/kg (8), which is equal to the RDA value for a very active woman (25). Energy consumption of the adolescent Greek female volleyball athletes in the present study also was less than the reported energy consumption of female track and field athletes (29), female adolescent swimmers (3), female rowers (28), and gymnasts, figure skaters, and runners (24). Our results agree with other studies showing that adolescent female athletes tend to consume a diet deficient in kilocalories (23).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although the NP consumed more kilocalories than the CP, both groups failed to consume the recommended kilocalories for female volleyball players of 44 kcal/kg (8), which is equal to the RDA value for a very active woman (25). Energy consumption of the adolescent Greek female volleyball athletes in the present study also was less than the reported energy consumption of female track and field athletes (29), female adolescent swimmers (3), female rowers (28), and gymnasts, figure skaters, and runners (24). Our results agree with other studies showing that adolescent female athletes tend to consume a diet deficient in kilocalories (23).…”
Section: Discussionsupporting
confidence: 78%
“…Our athletes' consumption of carbohydrates was 45.9% of the total energy intake, which is far less than the suggested 60% (16). Our athletes also had smaller CHO intake compared to the athletes of other sports, both aerobic and anaerobic (3,24,28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that were conducted prior to the establishment of the DRIs for iron in 2001 often used two-thirds of the former RDA, which was 15 mg/day (FNB 1989), as the definition of sufficient dietary iron intake. There is evidence that adolescent and collegiate female athletes in a wide variety of sports do not consume enough dietary iron (Beals 2002;Kim et al 2002;Papadopoulou et al 2002;Ziegler et al 2002;Gropper et al 2006); although others have reported that most female athletes consume adequate dietary iron (Steen et al 1995;Hinton et al 2004). However, as mentioned above, these discrepant results may be partially explained by differences in the value used to define adequacy-that is, use of the RDA (18 mg/day) versus the EAR (8 mg/day).…”
Section: Dietary Iron Intakes In Female Athletesmentioning
confidence: 96%
“…Studies that were conducted prior to the establishment of the DRIs for zinc in 2000 (RDA 1989) often used two-thirds of the former RDA, which was 12 mg/day, as the criterion for sufficient dietary zinc intake. Based on this criterion, there is some evidence that many adolescent and collegiate female athletes do not consume adequate dietary zinc (Steen et al 1995;Nuviala et al 1999;Beals 2002;Papadopoulou et al 2002;Ziegler et al 2002;Hinton et al 2004). …”
Section: Dietary Zinc Intakes Of Female Athletesmentioning
confidence: 97%